Civil War Mississippi : a guide - Ballard, Michael B. (University Press of Mississippi, 2000)
In the Civil War Mississippi experienced a protracted and devastating invasion, and Confederate and Union armies fought fiercely at Corinth, Holly Springs, Iuka, Port Gibson, Vicksburg, and many other sites throughout the state. With both tourists and Civil War buffs in mind, archivist Michael Ballard has written Civil War Mississippi: A Guide, the first comprehensive coverage of the war in the state. Containing easy-to-follow maps and a wealth of historical material, the book discusses the campaigns, the present-day battlefields, the battles, and the soldiers and generals who fought. The w.